Black women in white : racial conflict and cooperation in the nursing profession, 1890-1950 - Hine, Darlene Clark (Bloomington, Ind. : Indiana University Press, 1989)
This pathbreaking study analyzes the impact of racism on the development of the nursing profession, particularly on black women in the profession.
The origins of the Black hospital and nurse training school movement: an overview -- Northern Black hospitals and nurse training schools -- Training nurses in southern Black hospitals -- Black collegiate nursing education: a case study -- Racism, status, and the professionalization of Black nursing -- The politics of agency and the revitalization of the NACGN -- Black women in white -- We shall not be left out: World War II and the integration of nursing.
Includes bibliographical references (pages 241-254) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Umschulungswerkstätten für Siedler und Auswanderer; African American nurses -- History; Nursing -- United States -- History; United States -- Race relations -- History; Black or African American -- history; History of Nursing; Race Relations -- history; United States; Infirmières noires américaines -- Histoire; États-Unis -- Relations raciales -- Histoire; MEDICAL -- Nursing -- Issues; African American nurses; Nursing; Race relations; United States; Schwarze; Rassenkonflikt; Krankenpflege; Schwärze; USA; Verpleegkundigen; Rassenvraagstuk; Geschichte (1890-1950); African American nurses -- History; Geschichte -- 1890-1950; Nursing -- History -- United States; United States -- Race relations -- History; History